2021
DOI: 10.1155/2021/5167858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cold Chain Management Performance for Temperature-Sensitive Pharmaceuticals at Public Health Facilities Supplied by the Jimma Pharmaceuticals Supply Agency Hub, Southwest Ethiopia: Pharmaceuticals Logistic Management Perspective Using a Multicentered, Mixed-Method Approach

Abstract: Background. Effective and efficient cold chain management maximizes utilization of healthcare resources, reduces cold chain products wastage, and improves the quality of health services. It eventually guarantees that clients receive cold chain products they need at service delivery points. The objective of this study was to evaluate cold chain management performance for temperature-sensitive medicines at public health facilities in Southwest Ethiopia supplied by the Jimma Pharmaceuticals Fund and Supply Agency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Vaccine storage is said to be desirable/optimal when primary healthcare storage facilities met more than 70% storage condition criterion/parameters of cold chain storage [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Vaccine storage is said to be desirable/optimal when primary healthcare storage facilities met more than 70% storage condition criterion/parameters of cold chain storage [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adequate knowledge and skills in temperature monitoring are essential for healthcare workers to review health facility temperature data, establish response actions to avoid and minimise vaccine wastages during storage, and build community confidence in immunisation services. It was found that health workers have limited knowledge of proper cold chain management, with shallow scores in identifying vaccines that are mostly affected by freezing temperatures, compared to the study conducted in Ethiopia [21] and Nigeria [32]. The lack of knowledge might be attributed to a lack of health workers training on cold chain management to enable effective performance according to guidelines.…”
Section: Discussionmentioning
confidence: 96%
“…In the Expanded Program on Immunization (EPI), the cold chain system is used for storing, transporting, and distributing vaccines and other biologicals in recommended temperatures until they reach beneficiaries [ 13 , 21 ]. However, health workers and supervisors tend to emphasise protecting vaccines from heat damage, thus creating a risk of exposure to freezing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…We even go beyond this by packaging the insulin in special ice-filled packages and educating the patient about how to handle the insulin until they reach home. Feyisa et al (2021) noted that various methods could help ensure the availability of insulin through appropriate CCM, and this method ensures appropriate drug storage by setting a proper temperature of fewer than 41 degrees Fahrenheit [7]. Similarly, Bastani et al (2021) said that a cold supply chain was an effective technique that allows the long-term storage and management of insulin at different levels of its availability, leading to a decline in its shortage [8].…”
Section: Theme 2: Methods For Ensuring the Effectiveness Of The Suppl...mentioning
confidence: 99%
“…Keeping insulin at room temperature can be detrimental to its effectiveness and efficiency, while cold supply chain management (CSCM) of insulin can improve both. CSCM is the storage or transportation of items that must be preserved at temperatures below 5 degrees Celsius (41 degrees Fahrenheit) [7]. This definition may be applied to pharmaceuticals, vaccines, biological products, blood products, cultures, tissues, organs for transplantation, and foods and dairy products.…”
Section: Ccm Of Insulin To Improve Its Efficiency and Effectiveness I...mentioning
confidence: 99%